Patient’s Order Diet Management System - REBECCAROOBABATHY, RAVICHANDRAN (Universiti Malaysia Sarawak (UNIMAS), 2020)
Patient’s Order Diet Management System is a system created to improve the existing system that is used in the hospital to order a patient’s diet. This system is used by the dietician to recommend a suitable diet of the referred patients only. The recommended diet will be taken down by the diet aid to order the diet of that patient. The order diet form will be filled in by the diet aid, later they will distribute the diet (food) to the patient. The purpose of this system is to minimize the use of paper and reduce the hassle of the dietician for recommending the proper diet and diet aid to order the diet for the patient. Also, through this system, the user will be able to record all information regarding the recommended diet and order diet of those patients and it will be stored into the database. Hence, this project focuses more on the referred patients that will be reviewed by the dietician.